Analyzing Gender Inequality and Stereotypes in Foreign-Sourced ELT Textbooks at an Indonesian School: A Mixed-Methods Content Analysis - Swara, Sanditya Jati; Mambu, Joseph Ernest (VELES Voices of English Language Education Society, 2024)
This study investigates gender stereotypes in two ELT textbooks, "My Pals Are Here! English 1A" and "My Pals Are Here! English 2A," used at a school in Indonesia. Through content analysis, the study assesses the visual representations in these textbooks to identify gender stereotypes. A semi-structured interview was conducted with a teacher who uses these textbooks, focusing on her perceptions of gender-related issues. The findings reveal persistent gender inequality and stereotypes, with the textbooks frequently assigning unequal household roles and associating specific jobs with specific genders. Men are predominantly depicted in physically demanding roles, such as firefighters, farmers, astronauts, and pilots. In contrast, women are portrayed in roles that are suggested to require patience and perseverance, such as teachers, hairdressers, and nurses. The interview with the teacher indicated an awareness of gender equality issues; however, this awareness was not actively integrated into her teaching practices. This study highlights the need for more equitable gender representations in educational materials.